An Extract of Taro (Colocasia esculenta) Mediates Potent Inhibitory Actions on Metastatic and Cancer Stem Cells by Tumor Cell-Autonomous and Immune-Dependent Mechanisms - Kundu, Namita (Breast Cancer (Auckl), 2021)
The taro plant, Colocasia esculenta, contains bioactive proteins with potential as cancer therapeutics. Several groups have reported anti-cancer activity in vitro and in vivo of taro-derived extracts (TEs). We reported that TE inhibits metastasis in a syngeneic murine model of Triple-Negative Breast Cancer (TNBC). PURPOSE: We sought to confirm our earlier studies in additional models and to identify novel mechanisms by which efficacy is achieved. METHODS: We employed a panel of murine and human breast and ovarian cancer cell lines to determine the effect of TE on tumor cell viability, migration, and the ability to support cancer stem cells. Two syngeneic models of TNBC were employed to confirm our earlier report that TE potently inhibits metastasis. Cancer stem cell assays were employed to determine the ability of TE to inhibit tumorsphere-forming ability and to inhibit aldehyde dehydrogenase activity. To determine if host immunity contributes to the mechanism of metastasis inhibition, efficacy was assessed in immune-compromised mice. RESULTS: We demonstrate that viability of some, but not all cell lines is inhibited by TE. Likewise, tumor cell migration is inhibited by TE. Using 2 immune competent, syngeneic models of TNBC, we confirm our earlier findings that tumor metastasis is potently inhibited by TE. We also demonstrate, for the first time, that TE directly inhibits breast cancer stem cells. Administration of TE to mice elicits expansion of several spleen cell populations but it was not known if host immune cells contribute to the mechanism by which TE inhibits tumor cell dissemination. In novel findings, we now show that the ability of TE to inhibit metastasis relies on immune T-cell-dependent, but not B cell or Natural Killer (NK)-cell-dependent mechanisms. Thus, both tumor cell-autonomous and host immune factors contribute to the mechanisms underlying TE efficacy. Our long-term goal is to evaluate TE efficacy in clinical trials. Most of our past studies as well as many of the results reported in this report were carried out using an isolation protocol described earlier (TE). In preparation for a near future clinical trial, we have now developed a strategy to isolate an enriched taro fraction, TE-method 2, (TE-M2) as well as a more purified subfraction (TE-M2F1) which can be scaled up under Good Manufacturing Practice (GMP) conditions for evaluation in human subjects. We demonstrate that TE-M2 and TE-M2F1 retain the anti-metastatic properties of TE. CONCLUSIONS: These studies provide further support for the continued examination of biologically active components of Colocasia esculenta as potential new therapeutic entities and identify a method to isolate sufficient quantities under GMP conditions to conduct early phase clinical studies.